Immune Modulation Properties of Zoledronic Acid on TcRγδ T-Lymphocytes After TcRαβ/CD19-Depleted Haploidentical Stem Cell Transplantation: An analysis on 46 Pediatric Patients Affected by Acute Leukemia - Merli, Pietro; Algeri, Mattia; Galaverna, Federica; Milano, Giuseppe Maria; Bertaina, Valentina; Biagini, Simone; Girolami, Elia; Palumbo, Giuseppe; Sinibaldi, Matilde; Becilli, Marco; Leone, Giovanna; Boccieri, Emilia; et al. (Frontiers in Immunology, 2020)
TcRαβ/CD19-cell depleted HLA-haploidentical hematopoietic stem cell transplantation (haplo-HSCT) represents a new attractive platform for children affected by acute leukemia in need of an allograft and lacking a matched donor, disease recurrence being the main cause of treatment failure. The use of zoledronic acid to enhance TcRγδ lymphocyte function after TcRαβ/CD19-cell depleted haplo-HSCT was tested in an open-label, feasibility, proof-of-principle study. Forty-six children affected by high-risk acute leukemia underwent haplo-HSCT after removal of TcRαβ+ and CD19+ B lymphocytes. No post-transplant pharmacological graft-versus-host disease (GVHD) prophylaxis was given. Zoledronic acid was administered monthly at the dose of 0.05 mg/kg/dose (maximum dose 4 mg), starting from day +20 after transplantation. A total of 139 infusions were administered, with a mean of 3 infusions per patient. No severe adverse event was observed. Common side effects were represented by asymptomatic hypocalcemia and acute phase reactions (including fever, chills, malaise and/or arthralgia) within 24-48 hours from zoledronic acid infusion. The cumulative incidence of acute and chronic GVHD was 17.3% (all grade I-II) and 4.8% (all limited), respectively. Patients given 3 or more infusions of zoledronic acid had a lower incidence of both aGVHD (8.8% vs 41.6%, p=0.015) and chronic GVHD (0% vs 22.2%, p=0.006). Transplant-related mortality (TRM) and relapse incidence at 3 years were 4.3% and 30.4%, respectively. Patients receiving repeated infusions of zoledronic acid had a lower TRM as compared to those receiving 1 or 2 administration of the drug (0% versus 16.7%, p=0.01). Five-year overall survival (OS) and disease-free survival (DFS) for the whole cohort were 67.2 and 65.2%, respectively, with a trend towards a better OS for patients receiving 3 or more infusions (73.1% vs 50.0%, p=0.05). The probability of GVHD/relapse-free survival was significantly worse in patients receiving 1-2 infusion of zoledonic acid than in those given >3 infusions (33.3% vs. 70.6%, respectively, p=0.006). Multivariable analysis showed an independent positive effect on outcome given by repeated infusions of zoledronic acid (HR 0.27, p=0.03). These data indicate that the use of zoledronic acid after TcRαβ/CD19-cell depleted haploHSCT is safe and may result into a lower incidence of acute GVHD, chronic GVHD and TRM.